Ovarian Torsion in a Young Adolescent with Rokitansky Syndrome - Francesco Fedele; Giovanna Esposito; Andrea Busnelli; Fabio Parazzini (Hindawi Limited, 2024)
A case report of a premenarcheal patient with ovarian torsion and mullerian agenesis is presented. A 12-year-old prepubertal girl is presented with severe right lower quadrant abdominal pain and mild rebound. Laparoscopy showed mullerian agenesis and twisted right adnexa. Detorsion and cystectomy of the right ovary were done, and the ovary was fixed to the pelvic sidewall. The postoperative course was uneventful. An association between the lax attachment of the adnexa and torsion may be a contributing factor in this condition.